Dampak Pemanfaatan Biogas pada Rumah Tangga Petani di Kabupaten Boyolali - Surya Putra, Ahmad Romadhoni; Widodo, Widodo; Suparno, Nano (Universitas Muhammadiyah Yogyakarta, 2019)
This study aims to measure the impacts of biogas utilization in farmer’s household scale in Boyolali Regency. The survey toward 67 respondents of famer’s households in Samiran Village, Selo Subdistrict and Sruni Village, Musuk Subdistrict in Boyolali Regency were involved purposively. The farmer’s household involved in this study were the owners of biogas in household scale. For respondents having no biogas, it was required that they had known biogas in household scale. The data were analyzed using the impact evaluation model with Propensity Score Matching approach. The Treatment Effect Analysis shows that the biogas utilization in farmer’s household scale has significant impact on the decrease of Liquid Petroleum Gas (LPG) usage reaching until 2.54 kg/ month. Nevertheless, the impact on the firewood and organic fertilizer usage is insignificant. Through this study, it can be concluded that the utilization of household biogas among farmers has a significant impact on of the Liquid Petroleum Gas (LPG) usage.